Proposta e aplicação de um método para avaliação do grau de maturidade no escritório de projetos da unidade operacional de uma empresa multinacional do setor elétrico - Silva, Francisco Iranildo da (2019)
With globalization the competition between companies have increased. therefore, organizations seek methods and alternatives to enhance the performance of indicators and processes, improve management and monitoring of projects by implementing the pmo, or applying methodologies to define the maturity level that helped to achieve strategic results. therefore, this work has been elaborated which has a general objective to propose and apply an evaluation method to define the development level of office of projects of a department, and proposals / improvements to achieve the desired level. the methodology used is presented as applied research, with a quantitative and qualitative approach and with a purpose of a descriptive study. in the development of the work, the following technical procedures were used: bibliographical, documentary and case study. in the case study, six stages are developed, in order to understand the current maturity level and define the desired, and through the results, improvement proposals to raise the pmo maturity degree. the results have been discussed and analyzed, and the company has opened to execute the actions of the improvement plan to achieve the desired level of maturity of the departmental projects office.